Derivatization of Hyaluronan to Target Neuroblastoma and Neuroglioma Expressing CD44 - Giau Van Vo; Kummara Madhusudana Rao; Ildoo Chung; Chang-Sik Ha; Seong Soo A. An; Yang H. Yun (Pharmaceutics, 2024)
Therapeutics for actively targeting over-expressed receptors are of great interest because the majority of diseased tissues originate from normal cells and do not possess a unique receptor from which they can be differentiated. One such receptor is CD44, which has been shown to be highly overexpressed in many breast cancers and other types of cancer cells. While CD44 has been documented to express low levels in normal adult neurons, astrocytes, and microglia, this receptor may be overexpressed by neuroblastoma and neuroglioma. If differential expression exists between normal and cancerous cells, hyaluronan (HA) could be a useful carrier that targets carcinomas. Thus, HA was conjugated with resveratrol (HA-R), and its efficacy was tested on cortical–neuroblastoma hybrid, neuroblastoma, and neuroglioma cells. Confocal and flow cytometry showed these cells express CD44 and are able to bind and uptake HA-R. The toxicity of HA-R correlated well with CD44 expression in this study. Therefore, conjugating resveratrol and other chemotherapeutics to HA could minimize the side effects for normal cells within the brain and nervous system and could be a viable strategy for developing targeted therapies.